IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PLN PERSEROUNIT LAYANANPEMBANGKIT LISTRIK TENAGA AIR (ULPLTA) BAKARU DI DESA BAKARU KECAMATAN LEMBANG KABUPATEN PINRANG - Arham, Arham; Ernawati, Ernawati; Luthfi M, Mochtar (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2022)
This study aims to determine (1) the implementation of the Bakaru Hydropower Plant CSR program to the community. (2) Supporting factors in the implementation of CSR programs. (3) Inhibiting factors in CSR implementation. The type of research used is descriptive qualitative research with collection techniques, namely observation and interviews. This research was carried out at the Bakaru hydropower plant from October to November 2021. The results showed that (1) the Bakaru hydropower plant had implemented CSR programs from 2010-2021, except during 2016-2018 the Bakaru hydropower plant did not implement the CSR program because the proposed budget was made to the The Parent Unit was not approved because at that time the Parent Unit focused on Area Offices related to direct customer service distribution. (2) Supporting factors of CSR implementation are PLN as the authority holder, the village government as the one who knows the situation and needs of the community and the local community as the beneficiaries of the CSR program. (3) The inhibiting factors of CSR implementation are the less intensive communication between PLN and the community and the internet network factor.